Hubungan Lingkungan Kerja dengan Kepuasan Kerja Perawat - Marliani Marliani; Riswani Tanjung; R. Kintoko Rochadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to identify the relationship between the work environment and the job satisfaction of nurses in RSUD. Dr. Fauziah Bireuen. This research method is cross-sectional with a random sampling technique. The sample for this study was 138 nurses in the inpatient room at RSUD dr. Fauziah Bireuen. Data collection uses a questionnaire. Data analysis used Chi-square statistical test analysis. The research results showed a good work environment. Of the 83 respondents, 54 (65.1%) nurses said they were satisfied with their work and 29 (34.9%) said they were dissatisfied with their work. Of the 55 respondents, 23 nurses said they were satisfied with their work and 32 said they were dissatisfied. The results obtained were p = 0.007 < 0.05, meaning there was a relationship between the work environment and the job satisfaction of nurses in the inpatient room. In conclusion, there is a significant relationship between the work environment and job satisfaction of nurses in the inpatient room at RSUD dr. Fauziah Bireuen. Keywords: Job Satisfaction, Nurses, Work Environment.